Women academics in science and technology with special reference to Turkey - Saglamer G. (Women status in the Mediterranean: their rights and sustainable development, 2009)
Women face great difficulties in developing professional careers in equal opportunities to those of men in science-engineering-technology (SET), especially regarding their proportion and representation at the higher levels of hierarchical ladder. This multi-dimensional problem has been addressed by many researchers and remarkable outcomes have been disseminated by these researchers and research teams. In this presentation some of these outcomes and facts about women representation in SET will be outlined and discussed. Horizontal and vertical segregation for women academics is also widely analysed according to some important research projects' results such as ETAN. Comparative analysis on the representation of women in academia between OECD countries and some EU countries has been carried out under the umbrella of UNICAFE project which has been funded under the FP6 by EC. It has been demonstrated that Turkey is one of the leading countries among OECD and especially in EU countries in terms of women representation in academia in SET. Last section of the presentations has been devoted to the case study on Istanbul Technical University.
International Meeting on Women Status in the Mediterranean: their Rights and Sustainable Development, 2008/06/16-17, Bari (Italy)